Trajetória acadêmica e experiência de uma estudante estrangeira no curso de medicina no Brasil - Marcano, Oriana Alejandra Millan (Universidade Federal de São Carlos, 2025)
This Undergraduate Thesis seeks to encompass the author’s experience and personal development journey, as well as her professional growth, as a foreign student throughout the Medical program at the Federal University of São Carlos. It addresses the experiences, challenges, learning processes, progress, and achievements acquired over the six years of training. The narrative also explores and integrates themes such as social diversity, cultural adaptation and its challenges, the vulnerability of international students, and the construction of professional identity within the medical field. The study highlights the complexity of international students’ experiences regarding cultural adjustment, as well as the obstacles faced during medical training. It further concludes that the Federal University of São Carlos offers a program with teaching approaches and learning environments that are well suited to preparing qualified professionals, combining solid theoretical and practical knowledge with strong skills in providing humanized patient care.
Academic trajectory and experience of a foreign student in the medicine course in Brazil
Keywords: Intercâmbio; Medicina; Adaptação cultural; CIENCIAS DA SAUDE::MEDICINA; 3. Saúde e Bem-Estar